Monitoring of internal load, sleep, and well-being in relation to injury and illness in professional basketball - Burger, J.; Latzel, R.; Voit, T.; Matits, L.; Moser, O.; Henze, A.-S. (BMC Sports Science, Medicine and Rehabilitation, 2026)
Background Athlete health is essential for sustained performance in professional sport, with injuries and illnesses limiting both individual and team success. Although athlete monitoring is widely used to support load and recovery management and reduce injury risk, evidence linking training load, well-being and health outcomes in professional basketball is inconsistent. Holistic monitoring approaches may enhance the understanding of load-related health dynamics. Therefore, this study aimed to investigate the associations between internal load, sleep, and physical and mental well-being and the occurrence of injury and illness in professional male basketball players across a competitive season.